Shear performance of cold-formed steel shear walls with high-aspect-ratios. (October 2021) - Yan, Zhao; Cheng, Yu; Shicai, Chen; Ziqin, Jiang; Wenying, Zhang
Abstract: Shear walls of cold-formed steel (CFS) with high aspect ratios could be used in buildings with large openings such as doors and windows. However, the performance of CFS shear walls with high aspect ratios remains unclear due to limited test data. This research aimed to explore the mechanic performance and strength reduction factor of CFS shear walls with high aspect ratios through an experimental study. Five full-scale specimens were tested under monotonic loading, and the failure mechanism, bearing capacity, stiffness, ductility, and energy dissipation of the specimens were obtained. The test results indicated that shear walls with small aspect ratios typically fail as a result of connection damage to horizontal seams and corners, whilst shear walls with high aspect ratios commonly buckle at both the end stud and bottom track. As the aspect ratio increased, the initial stiffness and capacity decreased, while the energy dissipation per unit length increased due to greater flexibility. Ultimately, this study proposes a more reasonable design formula for strength reduction factors based upon a regression analysis of the test data. This will facilitate a more sustainable design approach, and fulfills current standards in engineering practice.